2007
DOI: 10.1021/ic7003613
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of Cis-Dihydroxylation and Epoxidation of Alkenes by Highly H2O2 Efficient Dinuclear Manganese Catalysts

Abstract: In the presence of carboxylic acids the complex [Mn(IV)2(micro-O)3(tmtacn)2]2+ (1, where tmtacn = N,N',N''-trimethyl-1,4,7-triazacyclononane) is shown to be highly efficient in catalyzing the oxidation of alkenes to the corresponding cis-diol and epoxide with H2O2 as terminal oxidant. The selectivity of the catalytic system with respect to (w.r.t.) either cis-dihydroxylation or epoxidation of alkenes is shown to be dependent on the carboxylic acid employed. High turnover numbers (t.o.n. > 2000) can be achieved… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
136
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 103 publications
(144 citation statements)
references
References 67 publications
6
136
1
Order By: Relevance
“…Recently, a bridged manganese(V) porphyrin dimer was shown to oxidize water into dioxygen, [20] and reversible O-O bond cleavage was observed for a manganese corrole system [21,22], and the design of novel, long-lived manganese(III) complexes, which can be a model of the precursor of the endogenous high-valent peroxo and oxo intermediates, has been published recently [23]. A special emphasis has been focused on manganese species as effective catalysts in the degradation reactions of many organic species [24,25]. In this study, a detailed account of the mechanistic features as well as the kinetic parameters for the oxidative transformation of phenothiazines by manganese(III) is provided.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a bridged manganese(V) porphyrin dimer was shown to oxidize water into dioxygen, [20] and reversible O-O bond cleavage was observed for a manganese corrole system [21,22], and the design of novel, long-lived manganese(III) complexes, which can be a model of the precursor of the endogenous high-valent peroxo and oxo intermediates, has been published recently [23]. A special emphasis has been focused on manganese species as effective catalysts in the degradation reactions of many organic species [24,25]. In this study, a detailed account of the mechanistic features as well as the kinetic parameters for the oxidative transformation of phenothiazines by manganese(III) is provided.…”
Section: Introductionmentioning
confidence: 99%
“…-0.2 V in the presence of carboxylic acids in water. de Boer et al [92] observed a similar effect of carboxylic acid in acetonitrile. The species formed initially upon reduction is the colourless Mn II Mn II complex 9c, which can undergo subsequent oxidation to form initially the Mn III 2 complexes 9d followed by a loss of H 2 O to form 9a ( Figure 7 and Figure 8).…”
Section: IImentioning
confidence: 76%
“…In the case of carboxylato bridged complexes based on the tmtacn ligand (1,4,7- [92] have shown by ESI-MS that the rate of exchange of the μ-O bridge is dependent on the substituent on the carboxylato ligands. For example, whereas for 7 in CH 3 (Figure 2).…”
Section: Rate Of Exchange Of Acetato Aquo and Oxido Ligands In Multimentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, manganese(III) is employed in water splitting during the light reactions of green plant photosynthesis [1] and in enzymatic and nonenzymatic redox catalysis in mammalian systems [2][3][4]. It is also a powerful one-electron oxidant and a versatile, selective redox catalyst frequently used in laboratory and industrial organic synthesis involving oxygen transfer reactions to alkanes, alkenes and compounds containing nitrogen and sulfur atoms as well as carbon-carbon bond generation [5][6][7][8][9][10][11][12][13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%